Collaboration To Strengthen Village Apparatus Finances And Regional Education Offices In Facing Education Fund Efficiency Policies - Abdjan, Wirawati; Aisyah, Siti; Wuryanta, Aloysius Gonzaga Eka Wenats; Lestari, Eko Budi; Randi, Randi (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract The author conducted discussions to obtain a scholarship with several village officials, namely Bobo Jiko Village, the North Maluku Education Office. The result if this article show that the collaboration between the Bobo Jiko village apparatus and the Higher Education Office is a perfect collaboration where the Village Apparatus acts as a policy initiator, the main source of finance, and a provider of data for people who are or want to continue higher education. While the Ministry of Higher Education functions as a network expansion, administrative licensing affairs, and program development Keyword : Village Aparatus Finance, Efficiency, Regional Education